Spatial Analysis of Regional Poverty Rates in Bali for the period 2016-2020 - Maha Yoga, Gede Agus Dian; Diputra, Gde Indra Surya (Jurnal Ekonomi Pembangunan, 2024)
Poverty is a severe issue for local governments, particularly in Bali. This study aims to investigate factors influencing the regional poverty rate in Bali Province between 2016 and 2020. In the primary data obtained from BPS Bali Province, spatial regression data approaches and analyses were used. The findings show that housing, access to technology, and availability of natural resources affect poverty rates. The poverty line in Bali in the period 2016–2020 fluctuated significantly. Urban and rural poverty levels are affected by the availability of rice. At the same time, non-food commodities are higher in rural areas regarding housing, religious ceremonies, and customs. The contribution of the food poverty line to the urban poverty line was 68.76% less than the contribution of the food poverty line to the rural poverty line, which was 69.74%. From 2016 to 2020, the districts of Buleleng, Karangasem, Klungkung, and Tabanan each had the highest poverty depth index. The poverty depth index in urban areas reached 0.653, and in rural areas, 0.753. The severity index for urban poverty is 0.154, which is lower than the severity index for rural poverty, which is 0.156.